Barrier-to-autointegration factor proteome reveals chromatin-regulatory partners. - Rocío Montes de Oca; Christopher J Shoemaker; Marjan Gucek; Robert N Cole; Katherine L Wilson (PLoS ONE, 2009)
Nuclear lamin filaments and associated proteins form a nucleoskeletal ("lamina") network required for transcription, replication, chromatin organization and epigenetic regulation in metazoans. Lamina defects cause human disease ("laminopathies") and are linked to aging. Barrier-to-autointegration factor (BAF) is a mobile and essential component of the nuclear lamina that binds directly to histones, lamins and LEM-domain proteins, including the inner nuclear membrane protein emerin, and has roles in chromatin structure, mitosis and gene regulation. To understand BAF's mechanisms of action, BAF associated proteins were affinity-purified from HeLa cell nuclear lysates using BAF-conjugated beads, and identified by tandem mass spectrometry or independently identified and quantified using the iTRAQ method. We recovered A- and B-type lamins and core histones, all known to bind BAF directly, plus four human transcription factors (Requiem, NonO, p15, LEDGF), disease-linked proteins (e.g., Huntingtin, Treacle) and several proteins and enzymes that regulate chromatin. Association with endogenous BAF was independently validated by co-immunoprecipitation from HeLa cells for seven candidates including Requiem, poly(ADP-ribose) polymerase 1 (PARP1), retinoblastoma binding protein 4 (RBBP4), damage-specific DNA binding protein 1 (DDB1) and DDB2. Interestingly, endogenous BAF and emerin each associated with DDB2 and CUL4A in a UV- and time-dependent manner, suggesting BAF and emerin have dynamic roles in genome integrity and might help couple DNA damage responses to the nuclear lamina network. We conclude this proteome is a rich source of candidate partners for BAF and potentially also A- and B-type lamins, which may reveal how chromatin regulation and genome integrity are linked to nuclear structure.